Dielectric characterization of lead zirconate-titane(PZT) /polyurethane(PU) thin film composite: Volume fraction, frequency and temperature dependence. (3rd March 2016) - Aboubakr, Sarah; Rguiti, Mohamed; Yessari, Madiha; Elballouti, Abdessamad; Courtois, Christian; Hajjaji, Abdelowahed
ABSTRACT: The Lead Zirconate-titane(PZT) ceramic is known by its piezoelectric characteristic, but also by its stiffness. The use of a composite based on a polyurethane (PU) matrix charged by a piezoelectric material, enable to generate a large deformation of the material, therefore harvesting more energy. This new material will provide a competitive alternative and low cost manufacturing technology of autonomous systems (smart clothes, car seat, boat sail, flag …). A thin film of the PZT/PU composite was prepared using up to 80 vol. % of ceramic. Due to the dielectric nature of the PZT, inclusions of this one in a PU matrix raise the permittivity of the composite. For the most of industrial applications, the composite will not be used at room temperature, and as the energy harvested from this new materials have a direct relation with their permittivity we have made a study about the variation of the permittivity at different temperature and frequencies.